A first meeting place: John Webber's An Interview Between Captain Cook and the Natives (January 1777). Issue 4 (2nd October 2017) - Simmons, Laurence
ABSTRACT: On 26 January 1777, on the first stage of his third voyage to the Pacific, James Cook anchored in Adventure Bay on what is now called Bruny Island, Tasmania. Cook encountered the local Nuonenne people on two occasions, the second of which was recorded in an unfinished drawing (possibly done on the spot) by the expedition's artist, John Webber. Comments in their journals from officers and sailors on board Cook's ships indicate that the European perceptions and representations of Aboriginal people were initially mediated by the explorers' stereotypical understanding of other races. However, through a close reading of a number of structural features of Webber's composition – symmetry, resemblances in opposition, chiasmus, a figure who acts as a spectatorial stand-in, spatialisation – it is argued that Webber's drawing recognises the Aboriginal people encountered by the British as individuals, attends to the dramaturgy of the encounter, and is marked in various ways by a powerful and grounded indigenous agency. It is proposed that anthropologist Marshall Sahlins' paradoxical aphorism 'structure of the conjuncture' might be used to illuminate and designate the particular quality of events, the 'indigenous countersigns', depicted by Webber in this drawing.